Pomiędzy konformizmem a wycofaniem - analiza strategii wchodzenia w dorosłość młodzieży polskiej i ukraińskiej = Between conformity and withdrawal - the analysis of strategies for entering into adulthood by Polish and Ukrainian youth - Długosz, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents results of the research conducted at the turn of the year 2012/2013 among high school graduates in Przemyśl and Drohobycz. The aim of the studies was to determine life plans and aspirations, and to indicate similarities and differences between the youth from both countries. On the one hand, the peripheral placement of this social category in the social structure may cause the effects of the crisis to influence the strategies for entering into adulthood.
Keywords: youth; borderland; peripheries; social change; entering into adulthood; strategies; młodzież; pogranicze; peryferie; zmiana społeczna; wchodzenie w dorosłość; strategia